Awareness of and satisfaction with LGBTQIA+ resources in Iceland - Ástrós Óskarsdóttir 1997- (2023)
People of marginalized sexual and gender identity, or LGBTQIA+ (Lesbian, Gay, Bisexual, Transgender, Queer/Questioning, Intersex, Asexual, and other marginalized identities), have been shown to experience poorer mental health and well-being than heterosexual and cisgender people. Resources like education, advocacy, visibility, social support, events and mental health services can have a positive impact on LGBTQIA+ people’s well-being and improve resilience. Iceland has shown an effort in being an LGBTQIA+ friendly place and various resources of support are currently available for LGBTQIA+ people. This study examined awareness of and satisfaction with those resources. An online questionnaire with 158 adult participants was used to measure participants’ awareness and their ratings of importance and satisfaction with available LGBTQIA+ resources. Findings suggest a high awareness of available resources, especially among LGBTQIA+ participants. Results also indicate that LGBTQIA+ participants find many of the available support resources more important than non-LGBTQIA+ participants. A potential for increase and improvement of available LGBTQIA+ resources was found, particularly for more education, legal protection and government action for LGBTQIA+ people in Iceland. Results underline the importance of providing the LGBTQIA+ with appropriate support resources and educate the public. Keywords: LGBTQIA+, Support, Resources, Awareness, Satisfaction Rannsóknir hafa sýnt að fólk sem tilheyrir jaðarsettum hópum út af kynhneigð eða kynvitund, eða hinsegin fólk, upplifi verri andlega heilsu og minni vellíðan en gagnkynhneigðir og sískynja einstaklingar. Hins vegar geta stuðningur og úrræði eins og fræðsla, stuðningur, sýnileiki, viðburðir og geðheilbrigðisþjónusta haft jákvæð áhrif á líðan og þrautseigju hinsegin fólks. Á Íslandi er boðið er upp á ýmis úrræði og fjölda möguleika til stuðnings fyrir hinsegin samfélagið. Þessi rannsókn kannar vitund um og ánægju með tiltæk úrræði. Með rafrænum spurningalista og 158 ...